Tantangan dan Peluang Usaha pada Koperasi Sektor Perikanan: Studi Lapangan KUD Minasari Pangandaran - Puspita Hermawan, Adi; Oktaviani, Christina; Ardiansyah, Fikky; Indra Praja, Gunawan; Agustina, Tri (Koaliansi : Cooperative Journal, 2025)
The Minasari Koperasi Unit Desa (KUD) has an important role in helping local fishermen increase their income through increasing production capacity and productivity, expanding employment opportunities, and expanding the marketing reach of fishery products. However, in the process KUD Minasari faces several challenges and opportunities that can affect the sustainability and growth of its business. This research aims to analyze the challenges and opportunities faced by KUD Minasari, a fisheries cooperative in Pangandaran Regency. The method used is descriptive qualitative with a field study approach based on primary data obtained through visits, interviews and internal document review. KUD Minasari faces a number of challenges, such as dependence on one business unit, namely the Tempat Pelelangan Ikan (TPI), low technology adoption, and limited digital marketing. Less active member involvement and non-compliance with cooperative rules are also problems that result in slow development of cooperatives. This research also found opportunities for business diversification, increased use of technology, and market expansion through digital marketing strategies. By utilizing the potential of other business units, cooperatives can reduce the risk of dependence on TPI.